The impact of clay-based hypoxia mimetic hydrogel on human fibroblasts of the periodontal soft tissue. (April 2019) - Müller, Anna Sonja; Gashi, Milot; Janjić, Klara; Edelmayer, Michael; Moritz, Andreas; Agis, Hermann
Thixotropic clays have favorable properties for tissue regeneration. Hypoxia mimetic agents showed promising results in pre-clinical models for hard and soft tissue regeneration. It is unclear if clays can be used as carrier for hypoxia mimetic agent in a periodontal regenerative setting. Here, we tested the response of human fibroblasts of the periodontal soft tissue to synthetic clay hydrogels and assessed hypoxia mimetic agent release. Cells were cultured on synthetic clay hydrogels (5.00%–0.15%). We assessed viability and differentiation capacity with resazurin-based toxicity assays, MTT staining, Live-Dead staining, and alkaline phosphatase staining. To reveal the response of fibroblasts to hypoxia mimetic agent-loaded clay hydrogels, cells were exposed to clay supplemented with dimethyloxalylglycine, deferoxamine, l -mimosine, and CoCl2 . Supernatants from hypoxia mimetic agent-loaded clay hydrogels were harvested and replaced with medium at hour 1, 3, 6, 24, 48, and 72. To reveal the hypoxia mimetic capacity of supernatants, vascular endothelial growth factor production in the fibroblasts was assessed in the culture medium. Our data show that clay did not induce relevant toxic effects in the fibroblasts which remained capable to differentiate into alkaline phosphatase-positive cells at the relevant concentrations. Fibroblasts cultured on clay hydrogel loaded with dimethyloxalylglycine, deferoxamine, l -mimosine, and CoCl2 remained vital, however, no significant increase in vascular endothelial growth factor levels was found in the culture medium. Only dimethyloxalylglycine-loaded clay supernatants taken in the first hours stimulated vascular endothelial growth factor production in fibroblasts. In conclusion no pronounced toxic effects of synthetic clay were observed. Supplementation with dimethyloxalylglycine leads to hypoxia mimetic activity. This pilot study provides first insights into the impact of synthetic clay on periodontal tissue.